Current Progress and Perspectives of CDC20 in Female Reproductive Cancers - Ni, Ke; Hong, Li (Current Molecular Medicine, 2023)
The cancers of the cervix, endometrium, ovary, and breast are great threats to women’s health. Cancer is characterized by the uncontrolled proliferation of cells and deregulated cell cycle progression is one of the main causes of malignancy. Agents targeting cell cycle regulators may have potential anti-tumor effects. CDC20 (cell division cycle 20 homologue) is a co-activator of the anaphase-promoting complex/cyclosome (APC/C) and thus acts as a mitotic regulator. In addition, CDC20 serves as a subunit of the mitotic checkpoint complex (MCC) whose function is to inhibit APC/C. Recently, higher expression of CDC20 has been reported in these cancers and was closely associated with their clinicopathological parameters, indicating CDC20 a potential target for cancer treatment that is worth further study. In the present review, we summarized current progress and put forward perspectives of CDC20 in female reproductive cancers.
Keywords: endometrial cancer